Estimated GFR and Incident Cardiovascular Disease Events in American Indians: The Strong Heart Study - Shara, Nawar M. (2012)
BACKGROUND: In populations with high prevalence of diabetes and obesity, estimating glomerular filtration rate (GFR) by using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation may predict cardiovascular disease risk better than by using the Modification of Diet in Renal Disease (MDRD) Study equation. STUDY DESIGN: Longitudinal cohort study comparing the association of GFR estimated using either the CKD-EPI or MDRD Study equations with incident cardiovascular disease outcomes. SETTING AND PARTICIPANTS: American Indians participating in the Strong Heart Study, a longitudinal population-based cohort with high prevalences of diabetes, cardiovascular disease, and CKD. PREDICTOR OR FACTOR: eGFR predicted using the CKD-EPI and MDRD Study equations. OUTCOMES: Fatal and nonfatal cardiovascular events, consisting of coronary heart disease, stroke, and heart failure. MEASUREMENTS: The association between eGFR and outcomes was explored in Cox proportional hazards models, adjusted for traditional risk factors and albuminuria; the net reclassification index and integrated discrimination improvement were determined for the CKD-EPI versus MDRD Study equations. RESULTS: Among 4549 participants, diabetes was present in 45%, cardiovascular disease in 7%, and stage 3–5 CKD in 10%. Over a median of 15 years, there were 1280 cases of incident CVD, 929 of incident coronary heart disease, 305 of incident stroke, and 381 of incident heart failure. Reduced eGFR (<90 mL/min/1.73 m2) was associated with adverse events in most models. Compared with the MDRD Study equation, the CKD-EPI equation correctly reclassified 17.0% of 2,151 participants without incident CVD to a lower risk (higher eGFR) category and 1.3% (n=28) were incorrectly reclassified to a higher risk (lower eGFR) category. LIMITATIONS: Single measurements of eGFR and albuminuria at study visits. CONCLUSIONS: Although eGFR based on either equation had similar associations with incident cardiovascular disease, coronary heart disease, stroke, and heart failure events, among those not having events, reclassification of participants to eGFR categories was superior using the CKD-EPI equation compared with the MDRD Study equation.